Between Egyptian nationalism and religion: Imagining the nation from below - Sultan, Yara Moussa (AUC Knowledge Fountain, 2015)
The January 25 revolution and the dramatic unfolding of events thereafter, have been a time of immense social, political and economic transformation in Egypt. Recent changes in political leadership, from the fall of Mubarak’s regime, to the Muslim Brotherhood’s (MB) ascent to power, and finally, to the landslide victory of the Armed Forces through Abdel Fattah el-Sisi’s assuming of the presidency, have brought to light some of the dynamics of mass politics in Egypt. These transformations made visible a wide array of expressions of collective and national belonging as the Egyptian people came into contact with ideologically differentiated ruling regimes. The Muslim Brotherhood became synonymous with Islamic rule and an Islamic state in Egypt. The Armed Forces on the other hand, presented themselves as the true and ultimate bearer of Egyptian nationalism. What these uncomplicated identifications miss, however, are the intermediate and transformative positionalities between the two spheres of religion and nationalism, as subjectively experienced by citizens. Therefore, the aim of this work is to explore and unpack citizens’ own constructions of nationhood and national belonging during the Muslim Brotherhood’s rule and their quick fall from power; a time when Islamists were seemingly gaining a historical grip on Egyptian politics and society. The construction of national sentiments during this transformative period is explored through the experiences of residents of one of Cairo’s working class neighborhoods; ‘Ain el-Sira.